Radiation dose to the operator during fluoroscopically guided spine procedures. - Roccatagliata, Luca; Presilla, Stefano; Pravatà, Emanuele; Cianfoni, Alessandro (Neuroradiology, 2017)
Purpose: Fluoroscopy is widely used to guide diagnostic and therapeutic spine procedures. The purpose of this study was to quantify radiation incident on the operator (operator Air Kerma) during a wide range of fluoroscopy-guided spine procedures and its correlation with the amount of radiation incident on the patient (Kerma Area Product-KAP). Methods: We retrospectively included 57 consecutive fluoroscopically guided spine procedures. KAP [Gy cm] and total fluoroscopy time were recorded for each procedure. An electronic dosimeter recorded the operator Air Kerma [μGy] for each procedure. Operator Air Kerma for each procedure, correlation between KAP and operator Air Kerma, and between KAP and fluoroscopy time was obtained. Results: Operator Air Kerma was widely variable across procedures, with median value of 6.4 μGy per procedure. Median fluoroscopy time and median KAP per procedure were 2.6 min and 4.7 Gy cm, respectively. There was correlation between operator Air Kerma and KAP ( r = 0.60), with a slope of 1.6 μGy Air Kerma per unit Gy cm KAP incident on the patient and between fluoroscopy time and KAP ( r = 0.63). Conclusion: Operator Air Kerma during individual fluoroscopy-guided spine procedures can be approximated from the commonly and readily available information of the total amount of radiation incident on the patient, measured as KAP.